Carrageenans from nuclear phases of subantartic Mazzaella laminarioides (Gigartinales, Rhodophyta) and graft copolymerization of alkali-modified carrageenan with acrylamide - Arias, Franco; Mansilla Muñoz, Andres Omar; Matsuhiro, Betty; Pavez, Jorge; Torres, Rodrigo; Yanez-Sanchez, Mauricio (My University, 2016)
Aqueous extraction of cystocarpic, tetrasporic, and vegetative individuals of Mazzaella laminariodes collected in the Magellan Ecoregion, Southern Chile, afforded sulfated galactans. Analysis by Fourier transform infrared spectroscopy (FT-IR) and by H-1 and C-13 NMR spectroscopy indicated that purified extracts from cystocarpic (CP) and vegetative individuals (VP) were mixtures of kappa/iota-type carrageenans and their precursors mu- and nu-carrageenans, whereas the aqueous extract from tetrasporic individuals was a lambda-type carrageenan. Alkaline treatment of CP and VP polysaccharides produced modified polysaccharides with lower content of sulfate groups and with a concomitant increase of 3,6-anhydrogalactose content; analysis by 2D H-1 and C-13 NMR indicated the presence of hybrid kappa-iota-carrageenans. Copolymerization of alkali-treated CP carrageenan with acrylamide was achieved by using ceric ammonium nitrate as the initiator; studies by NMR spectroscopy indicated grafting of polyacrylamide at position C-6 of beta-galactopyranosyl residues. Reaction of modified CP with acrylamide assisted by microwave irradiation in the presence of ammonium persulfate afforded a copolymer grafted at position C-2 of beta-galactopyranosyl residues.
Keywords: carrageenans; mazzaella laminarioides; nuclear phases; copolymerization